2021
DOI: 10.3389/fpsyg.2021.730724
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Meaning in Life in Older Men and Women: The Role of Dimensions of Frailty and Social Support

Abstract: Presence of meaning in life is an important component of eudemonic wellbeing while aging. While subjective health and interpersonal relationships are among important sources of meaning for older adults, less research has explored the gender differences in the potential contribution of these sources to the presence of meaning in late life. The current study aims to examine the associations of frailty dimensions (daily activities, health problems, and psychosocial functioning) and social support with the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition, we should encourage as many older people as possible to take part in regular and regular physical exercise. Some scholars believe that good health problems, psychosocial competence, and social support can be effective in enhancing older people's sense of meaning in life (Golovchanova et al, 2021). Other researchers have identified successful events experienced in life as an important factor in enhancing the level of self-esteem in older people (Rosi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we should encourage as many older people as possible to take part in regular and regular physical exercise. Some scholars believe that good health problems, psychosocial competence, and social support can be effective in enhancing older people's sense of meaning in life (Golovchanova et al, 2021). Other researchers have identified successful events experienced in life as an important factor in enhancing the level of self-esteem in older people (Rosi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang and colleagues (2022) advanced that meaning in life, for both men and women, is derived from prosocial behaviors or one's capability to be of service to others. Among older men and women, daily activities, health problems, psychosocial functioning, and social support contribute to their meaning in life (Golovchanova et al, 2021). It is interesting to underscore that certain factors that give meaning to life among men and women are reported in the scholarship since these factors remain unknown among LGBT + people.…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish study with 618 older adults confirmed a significant negative correlation between frailty and MIL ( 24 ), indicating that higher levels of meaning are associated with better health. Conversely, more debilitated older adults tend to perceive themselves as more useless, resulting in lower MIL.…”
Section: Introductionmentioning
confidence: 99%